Corregedores/Ouvidores e correições nos concelhos portugueses : um exemplo setecentista do Condado da Feira - Silva, Francisco Ribeiro da (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The duties of District Corregidors are described in its respective title of the Kingdom’s Ordinances. In spite of the fact that their fundamental action was carried out within the scope of the administration of justice, one can neither ignore nor underestimate its municipal management surveillance role in the municipalities of their District. Therefore, within this framework, one of the obligations of the Corregidors in each of the municipalities was their annual visit. The Auditor Magistrates in the Donee Lands had the same annual visit obligation. In this essay, one studies precisely the historical reach of the Corregidors’ visits that took place in the municipality of Vila da Feira, Feira County, between 1745 and 1766, and its influx in the municipal governance.